SELECTIVE AGGLUTINATION A POSSIBLE SUBSTITUTE FOR THE ABSORPTIVE TESTIN THE CLASSIFICATION OF BRUCELLA SALMONELLA OR THEIR ANTISERA - RUIZ CASTANEDA, MAXIMILIANO (HOSPITAL GENERAL, LABORATORIO DEL TIFO, CD. MEXICO, DF, MEX, 1958)
A method is described which shows agglutination due to "major" agglutinins in mixtures of homologous and heterologous agglutinogens. Suitable dilutions of brucella-serum capable of agglutinating both abortus and melitensis to the same titer, show preferen
J IMMUNOL
Keywords: AGGLUTINATION, ABSORPTIVE, TESTIN, CLASSIFICATION, BRUCELLA, SALMONELLA, ANTISERA; CIENCIAS MEDICAS; PATOLOGIA; PATOLOGIA CLINICA